2021
DOI: 10.1371/journal.ppat.1010152
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of T-cell dynamics during latent cytomegalovirus infection in humans

Abstract: Cytomegalovirus (CMV) infection has a major impact on the T-cell pool, which is thought to be associated with ageing of the immune system. The effect on the T-cell pool has been interpreted as an effect of CMV on non-CMV specific T-cells. However, it remains unclear whether the effect of CMV could simply be explained by the presence of large, immunodominant, CMV-specific memory CD8+ T-cell populations. These have been suggested to establish through gradual accumulation of long-lived cells. However, little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…This is contributed by the existence of memory cells [ 38 ]. Immunologists regarded the long-lasting B-cells or T-cells as “memory cells.” Experiments gradually demonstrated that although the so-called “memory cells” are some specific forms of immune cells [ 39 , 40 ], they have similar half-lives as normal CD8+ cells [ 41 ]. Therefore, maintaining antibody levels in “memory cells” should be explained as a state of equilibrium between decay and regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…This is contributed by the existence of memory cells [ 38 ]. Immunologists regarded the long-lasting B-cells or T-cells as “memory cells.” Experiments gradually demonstrated that although the so-called “memory cells” are some specific forms of immune cells [ 39 , 40 ], they have similar half-lives as normal CD8+ cells [ 41 ]. Therefore, maintaining antibody levels in “memory cells” should be explained as a state of equilibrium between decay and regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of CMV infection correlates with age and significantly impact the T cell compartment. ( 16 , 17 ) To enable us to compare age-related changes with those induced by CMV infection, our cohort was equally balanced by age and CMV infection status. Large shifts in cell type composition were correlated with CMV infection status, as highlighted by increased proportion of effector populations.…”
Section: Resultsmentioning
confidence: 99%
“…The frequent CMV activation induces antibodies and T‐cell clones to the virus, which are mostly of CD8 + EM and TEMRA origin (Fuchs et al, 2019 ). A recent study, however, showed that the changes in the T‐cell pool of CMV‐infected individuals cannot be explained by the presence of large numbers of CMV‐specific T‐cells suggesting that CMV infection may also affect the phenotype of non‐CMV specific CD8 + T‐cells (van den Berg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%